THREE-END TRAVELING WAVE FAULT LOCATION BASED ON ELECTROMAGNETIC DECOUPLING (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2026)
This study introduces a novel three-end traveling-wave-based fault location (TW-FL) method for transmission lines to improve fault location accuracy and speed. Unlike traditional approaches, it eliminates the need for traveling-wave velocity and line-parameter measurements by analyzing current surges at three terminals and exploiting the time-of-arrival (TOA) of fault-induced waves to compute the fault location. For validation, the velocity implicitly derived from the TOA formulation was compared with its theoretical value, achieving an estimation accuracy of up to 99.96%, confirming the internal consistency and robustness. The model attained maximum and minimum fault location errors of 0.36% and 0.0803%, respectively, over 100 km from terminal P, demonstrating superior accuracy relative to existing models. Simulations conducted in PSCAD/EMTDC under various fault conditions verified its robustness, while validation of the WSCC 9-bus system confirmed its speed and reliability in improving grid performance and reducing power outage.
Keywords: Three-end; Wave velocity; Time of arrival; Fault location; Transmission lines